Inventory Level Improvement in Pharmacy Company Using Probabilistic EOQ Model and Two Echelon Inventory: A Case Study - Farmaciawaty, Desy Anisya; Basri, Mursyid Hasan; Utama, Akbar Adhi; Widjaja, Fransisca Budyanto; Rachmania, Ilma Nurul (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. This research is aimed to maintain the inventory level in a two-echelon pharmacy company. The company is a pharmacy company that has 16 branches that operate in Bandung and the surrounding area. The company has a problem with its high inventory cost. To solve the problem, the authors compare two methods that suit the company condition, i.e., the decentralized system using probabilistic EOQ model and the centralization system using the multi-echelon inventory technique. We analyzed sales data and on-hand inventory data acquired from the company information system to perform the study. We limit the scope to the class A items only. We also assume the lead time, setup cost, and holding cost used in this study with the company's owner's consent. To conclude, using the decentralized system, the company will save 31% of their inventory cost, while using the centralization system with the multi-echelon technique, the company will be able to save 61% of their inventory cost. We recommend the company to refer to its competitive strategy before deciding which model it would be implemented. Keywords:  Centralization, Decentralization, Probabilistic Economic Order Quantity (EOQ), Multi-Echelon Inventory, Pharmaceutical Inventory Management